INTEGRASI KEILMUAN DALAM PENYELENGGARAAN STIKES DI PONPES QAMARUL HUDA BAGU LOMBOK TENGAH - Nurdin, Nurdin; Mukhtar, L (JURNAL PENELITIAN KEISLAMAN, 2013)
Presence of STIKES in Ponpes Qamarul Huda, indicating that integration of science is not discourses and the effort of academician of PTAI itself, but nowadays Pesantren has make a change much more in the based on epistemology compared than PTAI. To comprehend this phenomenon, the method used is descriptive qualitative. The result of research indicate, firstly, management of STIKES in Ponpes Qamarul Huda Bagu which has background by factor multi, that is social factor of social economics, religious paradigm, dynamics education of goodness external and internal of Ponpes Qamarul Huda, and social need toward of adequate health; secondly, various strategy has conducted for the integration of science is not yet reflected in systematic effort in integral and academic process; and third, the implication of various itself, the science structure in STIKES Qamarul Huda represent a adoption the structure health science whereas concern in Islamic education with Aswaja program as supplement which do not have significances. As Institute regulation the integration between public college and Ponpes Qamarul Huda is still limited in institute integration, it is not more integration as substantial that is integration science. Integration science still express in single model where Islam theology which is contained in Awaja still self supporting which still limited subject.